2002
DOI: 10.1128/jb.184.5.1340-1348.2002
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Type III-Secreted Proteins of Xanthomonas campestris pv. vesicatoria Are Encoded within the hrp Pathogenicity Island

Abstract: The Hrp type III protein secretion system (TTSS) is essential for pathogenicity of gram-negative plant pathogen Xanthomonas campestris pv. vesicatoria. cDNA-amplified fragment length polymorphism and reverse transcription-PCR analyses identified new genes, regulated by key hrp regulator HrpG, in the regions flanking the hrp gene cluster. Sequence analysis revealed genes encoding HpaG, a predicted leucine-rich repeatcontaining protein, the lysozyme-like HpaH protein, and XopA and XopD, which are similar in sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
183
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(194 citation statements)
references
References 47 publications
6
183
2
3
Order By: Relevance
“…xopN, xopQ, xopP, and the C terminus of xopF1 are conserved across Xanthomonas spp. (Table 2), and their GC content is comparable with that of the Xcv hrp cluster (8). These xop genes may be members of a ''core'' group of Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…xopN, xopQ, xopP, and the C terminus of xopF1 are conserved across Xanthomonas spp. (Table 2), and their GC content is comparable with that of the Xcv hrp cluster (8). These xop genes may be members of a ''core'' group of Xanthomonas spp.…”
Section: Discussionmentioning
confidence: 94%
“…xopC and xopO did not hybridize to many distant Xanthomonas spp., but have homologs in two tomato phytopathogens, Pst and R. solanacearum (Tables 1 and 2), suggesting that these genes may have been introduced into Xcv by horizontal gene transfer. In fact, the xopC gene is flanked by 62-bp IRs and multiple ORFs predicted to encode transposases and integrases (8). A peptide fragment with homology to the Xcc IS1479 transposase (29) was identified upstream of xopO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PIP-box that is 31 bases upstream of the -10 promoter motif has not yet been shown to function in HrpX control of expression of avrRxv [6]. Analysis of the genome of Xcv revealed that there are PIP-boxes upstream of coding sequences for genes that have no obvious association with pathogenicity and also, HrpX controlled genes that do not contain this motif [11,12,85]. More work has to be done to understand the role of the PIP-box.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to AvrRxv, there are three other AvrRxv family members present in Xcv. These are AvrBsT, XopJ and AvrXv4 [6,10,11], all of which are translocated to the host cell [8,12,13]. Genes with high levels of sequence similarity are also present in other plant pathogens [14][15][16][17][18], and in the plant symbiont Rhizobium [19].…”
Section: Introductionmentioning
confidence: 99%